2009
DOI: 10.1007/s10876-009-0246-5
|View full text |Cite
|
Sign up to set email alerts
|

Shape- and Size-Selective Preparation of Hectorite-Supported Ruthenium Nanoparticles for the Catalytic Hydrogenation of Benzene

Abstract: The cationic organometallic aqua complexes formed by hydrolysis of [(C 6 H 6 ) 2 RuCl 2 ] 2 in water, mainly [(C 6 H 6 2? , intercalate into white sodium hectorite, replacing the sodium cations between the anionic silicate layers. The yellow hectorite thus obtained reacts in water with molecular hydrogen (50 bar, 100°C) to give a dark suspension containing a black hectorite in which large hexagonally shaped ruthenium nanoparticles (20-50 nm) are intercalated between the anionic silicate layers, the charges of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Rutheniumsupported hectorite obtained by ion exchange has been reported by Shimazu et al using [7] for the intercalation. These materials show high catalytic activity for the hydrogenation of olefins [5] and of aromatic compounds [8,9]. The hydrogenation of furfuryl alcohol (FA) to give tetrahydrofurfuryl alcohol (THFA) is of great importance [10][11][12][13], but little information is available in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Rutheniumsupported hectorite obtained by ion exchange has been reported by Shimazu et al using [7] for the intercalation. These materials show high catalytic activity for the hydrogenation of olefins [5] and of aromatic compounds [8,9]. The hydrogenation of furfuryl alcohol (FA) to give tetrahydrofurfuryl alcohol (THFA) is of great importance [10][11][12][13], but little information is available in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of transition metal salts by sodium borohydride is a common method for the preparation of metallic nanoparticles that allows a certain control of the morphology, important for activity and selectivity for catalytic applications [38]. The reaction medium (organic solvents or water) is also decisive for the morphology of the nanoparticles [29,39,40]. Figure 2 shows the TEM images of nanoRu′@hectorite obtained under different conditions: The ruthenium nanoparticles formed by sodium borohydride reduction of the precatalyst in pure water without a substrate being present is depicted in Figure 2a, while Figure 2b shows the in situ generated ruthenium nanoparticles obtained during a catalytic run in aqueous solution from the precatalyst and sodium borohydride in the presence of quinoline as the substrate.…”
Section: Characterization Of the Catalyst Nanoru'@hectoritementioning
confidence: 99%
“…In our previous work, we developed a heterogeneous catalyst by intercalation of cationic benzene ruthenium complexes into hectorite, followed by reduction with molecular hydrogen to give a black solid containing metallic ruthenium nanoparticles intercalated in hectorite (nanoRu@hectorite) [27][28][29]. This material was found to catalyze the hydrogenation of quinoline with switchable selectivity, the reaction in water at 60 °C and 30 bar H 2 giving THQ, conversion and selectivity being at 99% [30].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles with controllable chemical and physical properties can conveniently be obtained by employing suitable organometallic precursors [24]. We have previously shown that the selectivity during catalytic hydrogenation reactions can be conveniently controlled with nano ruthenium, which was obtained from arene ruthenium complexes devoid of interfering chloride ions [21,[25][26][27][28][29][30][31]. In this work, dicationic aqua complex [Me(C6H4)Pr i )Ru(H2O)3] 2+ was used as a precursor to avoid the presence of contaminants on the surface of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%